DIVERSITAS DIATOM DI PERAIRAN TELUK BAYUR KOTA PADANG SUMATERA BARAT - SUSANTI, DIAN RAMA (IAIN Batusangkar, 2012)
This study had been done to determine the diversity of Diatoms in the waters of the Teluk Bayur Padang, West Sumatera. Diatom samples were collected using a plankton net from five different stations. Each station purposive sampling defined by land use considerations. The result was find 67 species of diatoms, 38 species including Centrales orders, 29 species including Pennales order Frequency of attendance 100% match Climacodiumbiconcavum and Eunotia Lunaris. The highest density of C.biconcavum was 15.22 ind./l in waters near Mount Meruwith the highes trelative density wasfound in the waters of Nirwana Gardensis equal to 15.90%. The highest density of E.Lunaris was 15.22 ind./l in Kasiak Island water sand the highest relative density was found in the same water samounted to 10.90%. The waters chemical physics assay, factorlevels of N-total are lower than the minimum limit of 0.116mg/l in waters near the fishing village of Teluk Bayur.Key Words: Diatom, Diversity